(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This research aims to analyze the nature of the news coverage provided by Al-Iraqiya Satellite Channel regarding the population census in Iraq, considering it a pivotal national issue with strategic dimensions related to developmental, economic, and social planning. Al-Iraqiya was specifically selected for this study due to its status as the official state-run channel, which grants it a central role in shaping public opinion and raising public awareness about the significance and future implications of the population census. The study adopted a descriptive-analytical approach, utilizing content analysis as a tool to deconstruct and monitor media treatment patterns within related news bulletins and programs over a defined time period. The analytical framework was distributed across several elements, including: type of coverage, frequency of reporting, angle of approach, sources used, in addition to evaluating the level of balance and objectivity in the presentation. The findings of the research revealed that Al-Iraqiya’s coverage was characterized by a noticeable focus on official and procedural aspects of the census, with a relative weakness in deep analytical and interpretive treatment. The media coverage also showed significant interest in political and economic dimensions due to their direct impact on citizens’ lives, alongside granting a reasonable space for the voices of citizens and civil society organizations. This contributed to enhancing plurality in the narrative and increasing public engagement with the issue. The study recommends the development of future media coverage by adopting a more comprehensive and in-depth approach that integrates both informational and analytical aspects, thereby contributing to raising public awareness and strengthening the role of media in supporting national population policies.